2019
DOI: 10.1097/rlu.0000000000002903
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET in Giant Cell Arteritis

Abstract: An 87-year-old man, without significant history, presented at the emergency department with recurrent episodes of fever and weight loss for several weeks without diagnosis, despite extensive routine investigations including conventional imaging. 18F-FDG PET/CT revealed strongly increased uptake in the peripheral vessels of the upper and lower limbs with relative sparing of the larger vessels. Temporal artery biopsy was positive for arteritis. The diagnosis of giant cell arteritis with mainly involvement of upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…En el último tiempo se ha agregado la tomografía por emisión de positrones (PET) que ayuda, en el contexto de una vasculitis de grandes vasos como la ACG, a diagnosticar la inflamación de los grandes vasos como la aorta. El estudio no es de utilidad para efectuar el diagnóstico de ACG, ya que las arterias temporales no presentan captación [73][74][75] . El tratamiento inicial en pacientes sin signos o síntomas orientativos de daño isquémico se realiza con corticoides vía oral a dosis de 40 a 60 mg con un descenso gradual en 9 a 12 meses.…”
Section: Discussionunclassified
“…En el último tiempo se ha agregado la tomografía por emisión de positrones (PET) que ayuda, en el contexto de una vasculitis de grandes vasos como la ACG, a diagnosticar la inflamación de los grandes vasos como la aorta. El estudio no es de utilidad para efectuar el diagnóstico de ACG, ya que las arterias temporales no presentan captación [73][74][75] . El tratamiento inicial en pacientes sin signos o síntomas orientativos de daño isquémico se realiza con corticoides vía oral a dosis de 40 a 60 mg con un descenso gradual en 9 a 12 meses.…”
Section: Discussionunclassified
“…A recent comparison with TAB demonstrated a sensitivity and specificity of 92% and 85% respectively [61, 62•]. It also may help detect the diagnosis in cases where the primary symptoms are in the limbs, although TAB is still required to confirm GCA [63] and can detect aortitis in both cranial GCA and large vessel GCA [64]. While the primary role of FDG-PET in GCA diagnosis has been the identification of large vessel inflammation, a recent study has demonstrated utility in assessment of medium-sized intracranial arteries [65].…”
Section: Mrimentioning
confidence: 99%
“…1 Lower extremity arteritis in GCA has rarely been reported. [2][3][4][5][6][7][8] A previous study reported fewer aortic involvement in elderly patients with GCA than younger. 9 This case was classified as large vessel vasculitis, because the arteries of the temporal, vertebral, femoral, tibial, and fibular are large vessels in accordance with the 2012 Revised International Chapel Hill Consensus Conference Nomenclature of Vasculitides.…”
mentioning
confidence: 99%
“…In Japan, 19.2% of patients with large-vessel vasculitis exhibit imaging findings in the iliac or femoral artery 1 . Lower extremity arteritis in GCA has rarely been reported 2–8 . A previous study reported fewer aortic involvement in elderly patients with GCA than younger 9 .…”
mentioning
confidence: 99%